Linking smallholders to emerging markets for livestock products: research and development opportunities - Ehui, Simeon K.; Lapar, Ma. Lucila; Paulos, Z. (International Livestock Research Institute, 2002)
The livestock revolution presents new and expanding opportunities for smallholder livestock producers. The increasing demand for livestock products in South-East Asia presents expanding market opportunities for livestock producers, particularly for smallholders. The paper discusses how to link smallholders to emerging markets for livestock products. Market access is the main topic of discussion. Possible measures that can be taken to facilitate access to markets for smallholders are listed. The paper ends with a brief discussion on ILRI research on this area.